The Development of Innovative Arabic Matriculation Learning Media Based on Google Sites to Improve The Arabic Proficiency of MAN 1 Pasuruan Students - Muhammad Ahsan Thoriq; Novita Kusumadewi; Mohammad Ahsanuddin (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
The big challenge for education in the 21st century is emphasizing technology in learning. In addition, learning Arabic matriculation in the 21st century must equip students with Arabic knowledge, skills, and perspectives. It can be achieved by using audio-visual integrated digital learning media. The research aims to produce the audio-visual media e-Arabic learning integrated to enhance students' proficiency in Arabic learning materials. This media development uses ADDIE development models. The subjects used were students of class X MAN 1 Pasuruan. The data collection instruments used are a questionnaire and pretest-posttests for qualitative and quantitative data. The data analysis used was descriptive quantitative percent and normality tests and the Paired Sample T Test assisted by IBM SPSS Statistics 25 software. The results of validating material and design get a percentage score over 90%, which falls into the category of totally worthy or perfectly valid by considering the advice from the validator. Based on test results, students get an average percentage of 86%. While the result of the testing t-sample test results state that the media e-Arabic learning proved capable of increasing student language proficiency. So the media e-Arabic learning was developed to improve students' skills and is pronounced especially worthy of use for learning.Keywords - E-Arabic Learning, Google Sites, Language Proficiency.